Relationships amongst science, ethics and polis in pre-modern times - Eddington, Ian (Curtin University, 2016)
The emergence of the Modern Age is depicted as a replacement of a long standing political philosophy by a distinctly new one. Foundational meanings are attributed to key terms Science, Ethics and Polis, nuance in these terms is traced against those attributed meanings, and the integrating impact of that nuance on relationships amongst key terms is interpreted as changing political philosophy. Speculative questioning reflection is expressed about the nature of the next Polis.